Robotic Subtotal Cholecystectomy in a Geriatric Acute Care Surgery Patient with Super Obesity - Diane Bronikowski; Dominic Lombardo; Connie DeLa’O; Nova Szoka (Case Reports in Surgery)
Introduction. Unique challenges exist with conventional laparoscopic operations in patients with super obesity (BMI>50). Limited literature is available regarding use of the robotic platform to treat patients with super obesity or acute care surgery patients. This case describes an interval robotic subtotal cholecystectomy in an elderly patient with super obesity and multiple comorbidities. Case Description. A 74-year-old male with a BMI of 59.9 developed acute cholecystitis. He was deemed excessively high risk for operative intervention due to concurrent comorbid conditions and underwent percutaneous cholecystostomy. After a few months, a cholangiogram demonstrated persistent cystic duct occlusion. The patient expressed interest in tube removal and elective interval cholecystectomy. After preoperative risk stratification and optimization, he underwent a robotic subtotal cholecystectomy with near infrared fluorescence cholangiography. The patient was discharged on postoperative day one and recovered without complications. Discussion. Obesity is a risk factor for acute cholecystitis, which is most commonly treated with conventional laparoscopy (CL). CL is technically restraining and difficult to perform in patients with super obesity. The body habitus of patients with super obesity can impair proper instrumentation and increase perioperative morbidity. In this case, robotic assisted cholecystectomy console improved surgeon ergonomics and provided support for proper instrumentation. Robotic, minimally invasive cholecystectomy approaches may reduce perioperative morbidity in patients with super obesity. Further studies are necessary to address the role of robotic surgery in acute care surgery patients with super obesity.